Proportional closeness estimation of probability of contamination under group testing. Issue 2 (3rd April 2018) - Malinovsky, Yaakov; Zacks, Shelemyahu
Abstract: The article is focused on the problem of estimating the probability p of individual contaminated sample, under group testing. The precision of the estimator is given by the probability of proportional closeness, a concept defined in the Introduction. Two-stage and sequential sampling procedures are characterized. An adaptive procedure is examined.